EFFECTIVE STRATEGIC LEADERSHIP IN HEALTH SERVICES - Mey Lona Verawaty Zendrato (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
Health services focus on quality of care to achieve high levels of productivity. Good quality of care can’t be separated from the actions of the leader in managing health service management. Strategies are needed by leaders to create good quality health services from all aspects. Strategic leadership directs the leaders to influence their members to achieve common goals. The purpose of the leadership strategy is to understand how leaders can influence the performance of their members in achieving organizational goals effectively. Effective means that it can have an effect, so that an effective leadership strategy is expected to have an influence on organizational activities. Effective leadership is not always owned by a leader. Leaders need to learn how to make their leadership effective. The method used in this research is literature study from several books and journals. The results of the analysis show that in organizational activities, effective strategic leadership is needed so that organizational goals can be achieved.